Scope and limits of libertarian populism in Latin America - JARQUÍN-RAMÍREZ, Mauro (Utopía y Praxis Latinoamericana, 2025)
The article analyses the way in which libertarian populism, a strategic alliance between libertarianism and the extreme right, is currently organised in Latin America. It argues that it is possible to find in the region an attempt to promote mass politics in regional right-wing and libertarian platforms associated with Trumpism. The article seeks to: a) account for the theoretical principles and assumptions of the strategic marriage between libertarianism and the extreme right; b) problematise its strategy of political interpellation; c) analyse its organisational structure; and d) briefly assess its scope and limitations. The findings show that the construction of libertarian populism is part of a strategic bet present since the 1990s in the circuits of American libertarianism. The paper concludes with a reflection on the urgency of discussing and understanding libertarian populism's bid to mobilise the masses.